Sleep Disorders In Children From 4 To 18 Years Age Group Reporting To A Tertiary Care Hospital - Agarwal, Gaurang; Ghuliani, Ranjit; Swarup, Praneta; Thapar, Rajeev Kumar; Kumar, Abhinit; Chavda, Kuldeepsinh; Sen, Aditya (Journal of Neonatal Surgery, 2025)
Background: Sleep disorders are a common occurrence in children, adolescents and can present in a myriad of ways. According to a various studies conducted on sleep disorders, sleep problems were present in 34% - 59% of the participants. The average sleep requirement of a child ranges from 16 to 18 hours during the first year of life and gradually decreases to 10 hours per night during childhood and adolescence. Sleep problems during infancy and early childhood are uncommonly recognized in pediatric practice, hence diagnosis and treatment of sleep disorders are challenging.Sleep disorders are indirectly represented and are associated with complaints related to the initiation and maintenance of sleep, bed wetting, sleep talking, sleepwalking, teeth grinding, and night terrors. Polysomnography study is gold standard technique to diagnose sleep disorders, however it is not feasible to use polysomnography study at a community level. To diagnose sleep disorders at a community level sleep questionnaires can be used, these questionnaires have been validated by the use of polysomnography studies, with the help of such questionnaires, it is feasible to identify sleep disorders at a community level. Method: Pediatrics Sleep Questionnaire (PSQ) was used in this study to diagnose sleep disorders. This Questionnaire, contains 31 questions, was translated and utilized in this study. Questions were put to the parents. Questions answered by the parents which reflected the condition of the child vis a vis the presence of sleep disorders if any before the child’s current illness for which he/she had reported to the OPD. Questions 1–23 are composed of items related to snoring, sleep related breathing disorders (SRBD), daytime sleepiness, and daytime behaviour problems. These questions consist of items that were proven to be valid by conducting surveys on patients with sleep breathing disorders with an apnea-hypopnea index (AHI) of 5 or greater in polysomnography studies as defined in the study by Chervin et al where a sleep disorder was diagnosed in children older than 2 years of age. The sensitivity was 0.81 and the specificity was 0.87 when diagnosing sleep disorder using this questionnaire. Among those in the validation study, 85% of patient’s diagnosed using polysomnography were diagnosed with sleep disorder. Patients who answered with ‘Yes’ to more than eight of questions 1–23, they were classified as suffering from generalised sleep disorder. Patients who answered with ‘Yes’ to questions 24, 25 or 26 or two of questions 26–31 was indicative of specific sleep disorders, namely, sleepwalking, bruxism, night terrors or insomnia respectively. We followed the same questionnaire of utilising the 31 questions to diagnose a sleep disorder. Additional information was asked to assess and identify the risk factors associated with sleep disorders. To identify and assess the risk factors for sleep disorders questions pertaining to the environment mentioned in the pro forma were asked. Result: The study was conducted in School of Medical Sciences and Research, Greater Noida. This study analyzed 345 participants, with a mean age of 8.12±2.73 years. The gender distribution showed a predominance of males (63.2%) over females (36.8%). In this study majority had subjects had 1-2 hours of screen time daily (63.5%), while a small proportion (8.2%) had 4+ hours of screen exposure. Most children engaged in the study had 1-2 hours of physical activity (80%), where as only 7.5% had less than 1 hour of activity. Generalized Sleep Disorder (26.7%) was the most common type of sleep disorder seen in this study where as Sleep Walking (4.9%) was the least common type of sleep disorder, Bruxism was seen in 12.2% of the subjects and Night Terror in 9.3% of the subjects. Obesity significantly increased the risk of generalized sleep disorder (OR = 11.3, p < 0.001). Higher screen time (≥3 hours) was strongly associated with sleep disorders (OR = 22.73, p < 0.001). Increased physical activity (>2 hours/day) was protective against sleep disorders (p < 0.001). The study highlights a strong correlation between high screen time, obesity, and sleep disturbances, while higher physical activity appears to be a protective factor against sleep disorders. Conclusion: This study reveals that there is a high frequency of sleep disorders in children age 4 to 18 years. This requires further research as the presence of sleep disorders not only effects the body’s physical growth but it also affects the psychological development of the body. Sleep disorders In children should not be ignored and must be kept as a top health priority of the growing age group